Pengaruh Aktivitas Fisik dan Perilaku Vulva Hygiene terhadap Keputihan pada Remaja Putri di Desa Gue Gajah Kabupaten Aceh Besar - Zaitun Zaitun; Risna Fazlaini; Salamah Salamah; Ummu Aiman (Public Health Journal, 2026)
Background: Adolescence is a transitional stage from childhood to adulthood characterized by significant physical, psychological, and social changes. These changes require special attention to prevent potential health problems, particularly those related to reproductive health. One of the most common reproductive health issues experienced by adolescent girls is vaginal discharge (leucorrhoea). This study aimed to examine the relationship between physical activity and personal hygiene with the incidence of vaginal discharge among adolescent girls in Gue Gajah Village, Aceh Besar Regency, in 2026. Methods: This study employed a descriptive-analytic research design with a cross-sectional approach involving 59 respondents. Data were analyzed to determine the association between physical activity, personal hygiene, and the incidence of vaginal discharge. Results: The findings revealed a statistically significant relationship between physical activity and the incidence of vaginal discharge (p = 0.028). Adolescent girls with high levels of physical activity were more likely to experience abnormal vaginal discharge (60.7%), whereas those with lower levels of physical activity predominantly experienced normal vaginal discharge (66.7%). Furthermore, a significant association was found between personal hygiene and the incidence of vaginal discharge (p = 0.003). Participants who maintained good personal hygiene were more likely to experience normal vaginal discharge (71.9%), while those with poor personal hygiene were more likely to experience abnormal vaginal discharge (66.7%). Conclusion: The results indicate that both physical activity and personal hygiene are significantly associated with the incidence of vaginal discharge among adolescent girls. Therefore, efforts should be made to enhance adolescents' awareness of maintaining proper personal hygiene and managing physical activity appropriately. In addition, educational institutions and healthcare professionals should collaborate to provide continuous reproductive health education in order to promote healthy behaviors among adolescents.